ANALISIS INTERFERENSI LEKSIKAL PADA KALANGAN USIA DEWASA MASYARAKAT DAYAK BIDAYUH DI BADAT LAMA (PERBATASAN INDONESIA-MALAYSIA) - Lilian Slow; Eko Fery Haryadi Saputro (Universitas Muhammadiyah Surakarta, 2020)
Lexical Interference commonly happens in a bilingualism society. The People of Dayak Bidayuh in the Badat Lama village is a part of bilingualism society. The languages that they used are the Bidayuh dialect and the Malaysia language. Most of the Badat Lama People masters the languages but not all of them. The adult masters the languages mostly. The mastering of Malaysia language affects their competence of Bahasa. The aim of this research is to analyze the error of speaking in Bahasa. The error that are being analysed are in word, phrase, and structure and they are called as lexical interference. This research used a qualitative and quantitative method and it was a survey research. The collecting data technique of this research was by interview record. The result of it shows that there are 17 respondents of 25 adult respondents do the lexical interference either, word, phrase, and structure. Then, eight of 25 adult respondents do not do lexical interference. And then, only one adult respondent cannot speak in Bahasa. It concludes that amount 68% of the adult respondents in Badat Lama did the Lexical Interference.Keywords: Lexical Interfernce, Badat Lama, Bahasa Indonesia.